Shoulder pain and wheelchair propulsion biomechanics in manual wheelchair users - Briley, S. J. (2021)
Introduction: Shoulder pain remains a common health concern among nonathletic and athletic manual wheelchair users. The biomechanical parameters of wheelchair propulsion are thought to be associated with shoulder pain symptoms, yet the specific relationship between shoulder pain and either daily or sports wheelchair propulsion biomechanics is currently not well understood. In this thesis, four experimental studies addressed daily and sports wheelchair propulsion biomechanics and sought to identify associations between shoulder pain and the biomechanical characteristics of propelling a wheelchair in manual wheelchair users.